Sodium Hypochlorite Pentahydrate (NaOCl·5H2O) Crystals as an Extraordinary Oxidant for Primary and Secondary Alcohols - Okada, Tomohide; Asawa, Tomotake; Sugiyama, Yukihiro; Kirihara, Masayuki; Iwai, Toshiaki; Kimura, Yoshikazu (Synlett, 2014)
Sodium hypochlorite pentahydrate crystals containing less free sodium hydroxide and sodium chloride have been developed as an improved oxidant. Primary and secondary alcohols have been oxidized to the corresponding aldehydes and ketones with NaOCl·5H2O in the presence of TEMPO/Bu4NHSO4. This new oxidation method does not require pH adjustment and is applicable to sterically hindered secondary alcohols.
Keywords: sodium hypochlorite pentahydrate; TEMPO; 1-Me-AZADO